10-million-years AGO: Argonaute on chromatin in yeast and human, a conserved mode of action? - Harel-Bellan, Annick (Landes Bioscience, 2013)
Whereas in yeast the function and mode of action of nuclear RNAi are well documented, mammalian nuclear RNAi is a matter of debates. Several papers support a role for nuclear Argonaute in alternative splicing. However, the molecular mechanism remains elusive. Here, we discuss the human nuclear RNAi mechanism in light of what is known of the yeast process.